Perceptions of external costs of dust fallout from gold mine tailings: West Wits Basin - Mpanza, Mbalenhle; Adam, Elhadi; Moolla, Raeesa (Clean Air Journal, 2020)
Mining is important for the South African economy, as it is for many developing African nations. In 2017, mining was reported to contribute 6.8 % to the South African GDP and provided more than 460, 000 jobs. Though mining adds an enormous amount of value to the country, it has significant impacts on the environment and the socio-economic factors of society. The well-documented environmental impact of mining operations on surface and groundwater systems, known as Acid Mine Drainage (AMD), is just one of these environmental impacts. There are also other impacts such as the pollution of agricultural soils, the creation of sinkholes and air pollution. For example, airborne dust remains a persistent problem in South African urban areas due to the climatic conditions, extensive surface mining, unrehabilitated tailings storage facilities and mineral processing. However, very little is reported on the socio-economic costs that are due to poor environmental management. Some scholars assert that despite the Mine Health and Safety Act, deposition monitoring guidelines and national dust regulations, South Africa still experiences persistent dust problems, especially in coal and gold mining districts. This paper investigates the effect of gold mining dust pollution in and around a Gold Mining Village, in South Africa. A quantitative and qualitative approach was used, where a questionnaire and interviews were conducted to examine the Gold Mine Village perceptions on dust pollution and their socio-economic environment. This paper further examines how poor and premature mine closure by liquidation results in unrehabilitated mine tailings and how this has significant impacts on the socio-economic status of individuals and surrounding businesses. The community being investigated in this study, perceives the dust fallout impact to be a socio-economic threat. The paper finds that the community believes it incurs medical financial expenditures due to treating respiratory-related diseases triggered by dust fallout.